2004
DOI: 10.1152/ajpheart.00563.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inotropic effects of ETBreceptor stimulation and their modulation by endocardial endothelium, NO, and prostaglandins

Abstract: Endothelin (ET)-1 acts on ETA and ETB receptors. The latter include ETB1 (endothelial) and ETB2 (muscular) subtypes, which mediate opposite effects on vascular tone. This study investigated, in rabbit papillary muscles (n = 84), the myocardial effects of ETB stimulation. ET-1 (10(-9) M) was given in the absence or presence of BQ-123 (ETA antagonist). The effects of IRL-1620 (ETB1 agonist, 10(-10)-10(-6) M) or sarafotoxin S6c (ETB agonist, 10(-10)-10(-6) M) were evaluated in muscles with intact or damaged endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Cardiac endothelial cells are potential targets for IMD in the heart and therefore likely modulators of its myocardial action. In fact, the role of these cells in the paracrine modulation of myocardial contractility, namely through the release of neurohumoral agents, such as NO and endothelin-1, among others, is well documented (3,20). Furthermore, previous immunocytochemical studies demonstrate that these cells express the CL/RAMP receptor system responsible for IMD biological action, although IMD expression is restricted to cardiomyocytes in rats and humans (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac endothelial cells are potential targets for IMD in the heart and therefore likely modulators of its myocardial action. In fact, the role of these cells in the paracrine modulation of myocardial contractility, namely through the release of neurohumoral agents, such as NO and endothelin-1, among others, is well documented (3,20). Furthermore, previous immunocytochemical studies demonstrate that these cells express the CL/RAMP receptor system responsible for IMD biological action, although IMD expression is restricted to cardiomyocytes in rats and humans (31).…”
Section: Discussionmentioning
confidence: 99%
“…The lower muscular end was fixed in a phosphorbronze clip, and the upper tendinous end was attached to an electromagnetic length-tension transducer (University of Antwerp, Antwerp, Belgium; Ref. 20). Preload was initially set between 3 and 4 mN according to muscle dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast to what happens with other vasodilating and negative inotropic pathways, like endothelin ET B receptor stimulation. In fact, in the same animal species, the endothelium dependent ET B -mediated negative inotropic effect is mediated by nitric oxide and prostaglandins (Leite-Moreira and Bras-Silva, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that selective ET B1 receptor stimulation slowed myocardial relaxation (decreased dT/dt min ) through the release of NO and prostaglandins, whereas there was a faster relaxation upon preferential ET B2 receptor stimulation [32]. More recently, we demonstrated that the lusitropic effect of selective ET B receptor stimulation is dependent in the integrity of the endocardial endothelium, being negative when it is intact and positive when it is damaged [32].…”
Section: The Effects Of Et-1 On Myocardial Relaxationmentioning
confidence: 90%
“…ET A receptor activation evokes vasoconstriction [41], mitogenesis [46] and increased inotropism [22,25] whereas ET B receptor stimulation is associated with vasodilatation and growth inhibitory effects [40] associated with apoptosis [47]. The latter was further subdivided in ET B1 and ET B2 receptor subtypes: the ET B1 receptor is predominantly expressed in the vascular and endocardial endothelium and its stimulation elicits vasodilatation [12] and a negative inotropic effect [32] and the ET B2 receptor is located on vascular smooth muscle and myocardial cells, mediating vasoconstriction [59] and positive inotropism [32]. The ET B receptor is also responsible for the pulmonary clearance [15] and endothelial reuptake [48] of circulating ET-1.…”
Section: Endothelinmentioning
confidence: 99%